(untitled) (Journal of Global Humanities and Social Sciences, 2023)
This paper first introduces the research background of financial risks and corporate governance structure, using a sample of A-share companies listed in Shanghai and Shenzhen Stock Exchange from 2016 to 2018. It applies Z-score to measure financial risks and finds some quantitative methods to measure the factors in the corporate governance structure. This paper uses multiple linear regression model to analyze the correlation between financial risks and the corporate governance structure. The results show that ownership concentration, executive shareholding percentage and executive compensation have the most significant influence on financial risks and all of them are negatively correlated with financial risks. Therefore, we recommend companies to improve the non-executive director mechanism of listed companies, to maintain a relatively concentrated ownership structure, and to take effective incentive mechanism for executives. These recommendations can help companies better manage financial risks.